CENSOR: Cloud‐enabled secure IoT architecture over SDN paradigm. (28th November 2018) - Conti, Mauro; Kaliyar, Pallavi; Lal, Chhagan
Summary: The cyber‐security threats to low‐cost end‐user devices could severely undermine the expected deployment of Internet of Thing (IoT) solutions in a range of real‐world applications such as environment monitoring, transportation, and manufacturing. Additionally, the huge amount of data generated by these devices posses new challenges concerning tasks such as efficient information acquisition and analysis, decision making, and action implementation. In this paper, we propose CENSOR, a novel cloud‐enabled secure IoT network architecture based on SDN paradigm. We discuss the significant benefits as well as challenges that are inherent while performing integration of SDN and IoT in CENSOR. We show that the emerging software‐based networking features combined with the cloud computing solutions can significantly improve the security and communication reliability in the target IoT scenarios. In particular, to provide the adequate security measures in the network, CENSOR uses a lightweight and scalable software remote attestation scheme, which ensures the integrity of the software that is being executed by the IoT devices to achieve the application specific goals in the network. We further discuss the improvements in data communication and data overhead that can be achieved in CENSOR due to its convergence with the cloud computing (at back‐end) and fog computing services (at edge routers or front‐end). A Smart City use‐case has been considered as a target IoT scenario to analyze the feasibility and effectiveness of CENSOR concerning the communication security and the network scalability parameters. Additionally, we provide future research directions along with the recent industry initiatives that include open issues in the integration and deployment of cloud‐enabled SDN‐based IoT networks.